Fred Davis, Sailor, sings sea shanties and tells tales of the sea, c1967 - Michell, Robert (1967)
The Robert Michell Collection consists of Papers relating to Queensland Folk Federation and folk festivals: correspondence; posters; newspaper clippings; song lyrics; record lists; business correspondence of Queensland Folk Festival; minutes of meetings; miscellaneous folk festival programmes; audio tapes of oral history interviews and performances.